2016
DOI: 10.1001/jamaoncol.2016.0483
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Diagnosis of Mental Disorders Immediately Before and After Cancer Diagnosis

Abstract: IMPORTANCE Psychiatric comorbidities are common among patients with cancer. However, whether or not there is increased risk of mental disorders during the diagnostic workup leading to a cancer diagnosis was unknown.OBJECTIVE To examine the relative risks of depression, anxiety, substance abuse, somatoform/conversion disorder, and stress reaction/adjustment disorder during the periods before and after cancer diagnosis compared with individuals without cancer. DESIGN, SETTING, AND PARTICIPANTS Nationwide matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
110
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 39 publications
18
110
4
4
Order By: Relevance
“…(2013) found that suicide occurred on average 5.6 years after cancer diagnosis . Notably, even 10 years after cancer diagnosis the patients still have elevated relative rates of mental disorder and suicide mortality …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) found that suicide occurred on average 5.6 years after cancer diagnosis . Notably, even 10 years after cancer diagnosis the patients still have elevated relative rates of mental disorder and suicide mortality …”
Section: Discussionmentioning
confidence: 99%
“…34 Notably, even 10 years after cancer diagnosis the patients still have elevated relative rates of mental disorder and suicide mortality. 37 The increased OR of suicide at the early phase of cancer diagnosis can be attributed to physical distress, functional limitation and the devastating effects of cancer treatment. 38 Korfage et al found that the mental health of patients with prostate cancer was most intensely affected within the first 6 months.…”
Section: Cancer Epidemiologymentioning
confidence: 99%
“…However, for a subgroup of survivors, anxiety, depression, fears and distress can linger for up to 10 years after treatment. 107 For some of the issues discussed such as FOR, no standardized definitions exist, which makes comparing research results difficult. 108 More research is needed with diverse survivors on many levels: types and stages of cancer, racial/ethnic diversity, sexual minorities, and rural survivors to name a few groups.…”
Section: Future Considerations/summarymentioning
confidence: 99%
“…Stress levels seem to be elevated as soon as a suspicion of cancer is raised and the waiting time before a final diagnosis may be equally stressful as the post-diagnostic period [1,2]. We recently demonstrated a marked increase in risk for different psychiatric disorders during the six months before prostate cancer diagnosis, highlighting the potential impact of emotional stress experienced while waiting for the diagnosis [3].…”
mentioning
confidence: 99%
“…For self-reported stress symptoms, we assessed the levels of depression and anxiety with the Hospital Anxiety and Depression Scale (HADS), self-evaluated distress with the National Comprehensive Cancer Network (NCCN) distress thermometer, and sleep quality and disturbances with theÅkerstedts Karolinska Sleep Questionnaire. A self-rated sleep quality score (1)(2)(3)(4)(5) assessment scales, a higher value indicated a worse outcome. From randomization to first urologist visit, the depression score (HADS) was found to increase slightly in the usual care group while it decreased in the fast-track group (Table 1).…”
mentioning
confidence: 99%